“Nok”. A Phytosterol-Based Amphiphile Enabling Transition Metal-Catalyzed Couplings in Water at Room Temperature - Klumphu, Piyatida (2014)
[Image: see text] The third generation designer amphiphile/surfactant, “Nok” (i.e., SPGS-550-M; β-sitosteryl polyoxoethanylsuccinate), soon to be commercially available from Aldrich, can be prepared in two steps using an abundant plant feedstock, β-sitosterol, together with succinic anhydride and PEG-550-M. Upon dissolution in water it forms nanomicelles that serve as nanoreactors, which can be characterized by both cryo-TEM and dynamic light scattering analyses. Several transition metal-catalyzed reactions have been run under micellar conditions to evaluate this surfactant relative to results obtained in nanoparticles composed of TPGS-750-M (i.e., a second generation surfactant). It is shown that Nok usually affords yields that are, in general, as good or better than those typically obtained with TPGS-750-M, and yet is far less costly.